Pakistan’s Counter-Terrorism Narrative and Non-Traditional (Holistic) Security Paradigm with Civic Engagement - Umer Khayyam; Syed Shah; Fariha Tahir (NUST Journal of Social Sciences and Humanities)
The woes of terrorism and extremism pose a threat to the stability, economic development and human growth of nations. It, therefore, remains a serious concern for the state to rethink its strategies towards bringing stability. This paper, on deploying content analysis technique, explores the traditional security paradigm as a state-centric approach under the diverse concept of security. The non-traditional approaches; Buzan’s holistic perspective of a national security complex, Mehbub-ul-Haq’s human security notion and Mohammed Ayoob’s concept of weak state, are scrutinized to study the actual and potential role of civic engagement towards constructing an effective counter-terrorism narrative of Pakistan. It is established that due civic engagement has the potential to counter the extreme dogmas through collaborative efforts at home. It can also address the wrong perception about Pakistan’s inefficient counter-terror measures at the regional and global level.